2011
DOI: 10.1111/j.1464-410x.2011.10408.x
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D3 cryosensitization increases prostate cancer susceptibility to cryoablation via mitochondrial‐mediated apoptosis and necrosis

Abstract: Objectives To investigate the effect and molecular mechanisms of action of Vitamin D3 (VD3) as a neo-adjunctive agent before cryosurgery in an effort to increase treatment efficacy for prostate cancer (CaP). To eliminate the potential for disease recurrence that exists at the periphery of the freeze lesion, where temperatures may be insufficient to destroy both androgen-sensitive (AS) and androgen-insensitive (AI) CaP. Methods Human CaP cells, LNCaP, were each genetically altered to express the AS an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 43 publications
0
37
1
Order By: Relevance
“…It is important to understand the model utilized and recognize the benefits and limitations in order to frame the results. Several studies have shown that the distribution of the -20°C and -40°C critical isotherms is often restricted to the center of the frozen mass (closest to the cryoprobe), thereby comprising less than 35% and 20% of the frozen mass, respectively (53)(54)(55)58,61,67) The typical freeze times reported in these and other studies range from 5 to 10 minutes which are applied in multiple (repeat) freeze/ thaw scenarios. While limited, these data provide a reference point for comparison of modern technologies.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…It is important to understand the model utilized and recognize the benefits and limitations in order to frame the results. Several studies have shown that the distribution of the -20°C and -40°C critical isotherms is often restricted to the center of the frozen mass (closest to the cryoprobe), thereby comprising less than 35% and 20% of the frozen mass, respectively (53)(54)(55)58,61,67) The typical freeze times reported in these and other studies range from 5 to 10 minutes which are applied in multiple (repeat) freeze/ thaw scenarios. While limited, these data provide a reference point for comparison of modern technologies.…”
Section: Discussionmentioning
confidence: 84%
“…The data presented herein suggests that the SCN epicardial cryoprobe provides for the rapid delivery of an effective cryoablative dose to the target tissue using the ex vivo models evaluated. The data demonstrate that the delivery of a "thermal dose" of -30°C [59,[60][61][62][63][64][65][66][67][68] across tissue ranging from 5 mm to 1 cm in thickness under high (37°C) circulating heat loads in less than 2 minutes. Analysis of the thermal spread of the lethal temperatures during a 2-minute freeze was limited to within 5 mm of the probe surface thereby resulting in the creation of a defined linear ablation zone.…”
Section: Discussionmentioning
confidence: 99%
“…Antifreeze proteins have been shown to affect the rate and morphology of ice crystal formation and increase cell destruction in a prostate cancer grown in mice and rats [84,99]. Vitamin D 3 has been shown in cell culture and animal studies to be a highly effective cryosensitizing agent [12]. While diverse in nature and specific mechanisms (pathways) of action, a common theme of enhanced therapeutic outcome has emerged through the use of adjunctive pretreatment of cancer prior to cryoablation.…”
Section: Adjunctive Therapymentioning
confidence: 99%
“…Through various in vitro , in vivo , and clinical reports, improved cancer destruction at mild sub-freezing temperatures following brief low dose exposure to general or specific apoptotic inducing agents has been shown. In some cases, such as the use of vitamin D 3 as a sensitizing agent, complete prostate cancer cell death has been demonstrated following freezing to temperatures as warm as −10°C in both in vitro and in vivo models [12,61,111]. …”
Section: Adjunctive Therapymentioning
confidence: 99%
See 1 more Smart Citation